REKONSTRUKSI HERMENEUTIKA DALAM PENAFSIRAN AL-QUR’AN: STUDI KRITIS TERHADAP PARADIGMA TAFSIR MODERN - Ibadurrahman; Suwanda; Hikmatul Luthfi (Adisam Publisher, 2026)
This study aims to examine the concept of hermeneutics in the interpretation of the Qur’an and to analyze the epistemological problems that arise within the paradigm of modern Qur’anic exegesis. The background of this research is based on the growing use of hermeneutics as an interpretive approach in Qur’anic studies, which has generated debates between traditional and modern perspectives. This research employs a qualitative approach with a library research method and utilizes content analysis and critical analysis as analytical tools. The findings indicate that hermeneutics contributes to enriching interpretive methods through contextual approaches; however, it also has the potential to produce relativism of meaning due to the dominance of the interpreter’s subjectivity. Therefore, a reconstruction of hermeneutics is necessary, integrating contextual approaches with the fundamental principles of classical Qur’anic exegesis. This reconstruction emphasizes a balance between textual and contextual dimensions while maintaining the authority of divine revelation as the primary foundation in interpreting the Qur’an. Thus, it is expected to develop an interpretive model that is relevant to contemporary developments without neglecting the established traditions of Islamic scholarship.